PREDICTING LUNAR ECLIPSES IN NORTHERN LATITUDES BY NAKED EYE OBSERVATION. Issue 2 (14th December 2020) - Lee, Charles; Reilly, Thomas
ABSTRACT: We investigate methods which may have been found appropriate for predicting lunar eclipses in northern Europe, where naked‐eye astronomy has to be adapted to conditions, which are different from those found at lower latitudes and in places with less cloud cover. The ecliptic is lower in the sky, and transient phenomena cannot reliably be observed under these astronomical viewing conditions. We consider those techniques, which only require the use of objects made of wood, stone and soil, which use no written records, and which require no understanding of celestial mechanics. We show that it should have been possible to answer the question 'Is there going to be a lunar eclipse, either tonight or tomorrow night?' with surprising accuracy. We include an analysis of the nature of some of the artefacts, which may have been helpful in doing so.